ESTIMATION OF OUTWARD MIGRATION VOLUME OF UKRAINIAN POPULATION BASED ON UNITED NATIONS DATA - Zhuk, R. (Socio-economic relations in the digital society, 2021)
The aim of the study is to search, systematize and process statistical data that can be further used for quantitative analysis of factors influencing external labor migration, as well as to analyze the impact of external labor migration on the economy of Ukraine. The paper considers quantitative analysis of outward migration volume of Ukrainian population. Getting reliable data about international migration is complicated because of lack of efficient mechanisms for measuring its scale. Official country statistics do not provide reliable information because not all persons who leave the country indicate the true purpose of their travel abroad on the border crossing. It reviews the available sources of information regarding international migration. It uses the data from receiving countries as they are more meticulous in recording numbers and purpose of arriving migrants. United Nations Organization collects such data and publishes them every 5 years. The number of long-term migrants from Ukraine during 2000—2019 was estimated. For estimation we used statistics of migrants in particular years and deaths statistics in relevant countries. This approach allowed to estimate the absolute numbers and dynamics of migrants volume using the unified UN methods for measuring this process across countries. We studied changes in migrant numbers in every 5-year period between 2000 and 2019 and identified the countries which received the most migrants from Ukraine over this time span. It is likely that the number of labor migrants from Ukraine will continue to grow and the process of labor migration will have an increasing impact on the domestic economy. After all, migrant workers spend part of the money they earn in Ukraine, either directly or by making money transfers to their relatives and friends. Thus, the money they earn can indirectly increase the level of consumption in the country and improve living standards.